The Impact of Hybrid Work Management on Employee Engagement among Knowledge Workers - Sheue Hui Lim; Yong Xiang Loh; ZiChen Liu; Kar Xi Loh; Kah Kei Loke; Aditi Dixit; Tanya Rai; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
The widespread adoption of hybrid work arrangement has changed how organizations in Malaysia manage their employees. A key predictor of employee work engagement is difficulties in supervision, which contributes empirical evidence to the limited hybrid work literature in emerging economies. This study examined how hybrid work management influences employees’ overall engagement. The research objective it to investigate the impact of hybrid work management on employee engagement. The quantitative survey involved 100 respondents, and the collected data were analyzed using SPSS. The multiple regression analysis results reveal that the hybrid work can improve work-life balance, increase work performance and develop a better communication. However, there are challenges such as perceived burnout, difficulties in supervision and communication gaps. These findings also show that, when appropriate managerial support is provided, hybrid work is beneficial for both employees and organizations. In conclusion, hybrid work should be developed with clear policies. Organizations should strengthen communication and team connection by setting a clear meeting rules, create new way of collaboration, and provide managerial support to sustain a long-term employee engagement.